Navigating talent management in public sector organizations: An examination of distributive justice and managerial challenges on career satisfaction - Yoshinta, Dian Okta; Wijoyo, Suparto; Suhariadi, Fendy (Edelweiss Applied Science and Technology, 2025)
This study empirically investigates the impact of talent management practices on the career satisfaction of Civil Apparatus/Aparatur Sipil Negara (ASN), the civil service employees in Indonesia. This study aims to analyze how distributive justice serves as a mediating variable and how managerial challenges act as a moderating variable in this relationship. Using a quantitative approach, we distributed questionnaires to 170 respondents and employed partial least squares (PLS) analysis to test our hypotheses and validate the theoretical model. The results indicate that ASN career satisfaction has a mean score of 3.973, suggesting substantial satisfaction with career development, achievement, and recognition. Distributive justice also received a high score of 3.885, reflecting employees’ perceptions of fair distribution of rewards, benefits, and opportunities. Inclusive talent management practices received a high score of 3.983, reflecting employees’ perceptions of equitable talent development opportunities. However, management challenges had a low mean score of 2.348, highlighting barriers such as resistance to change and limited resources that hinder talent management initiatives. Exclusive talent management practices had a moderate mean score of 3.246, suggesting some effectiveness but indicating areas for improvement. In summary, the findings highlight the importance of inclusive talent management practices in promoting fairness and career satisfaction. However, management challenges may hinder the effectiveness of these practices, particularly in exclusive talent management settings. Practically, this study suggests that organizations can provide managers with adequate training and resources to implement inclusive and equitable talent management strategies that promote both distributive justice and employee career satisfaction.